Clinical trial simulations applications and trends - Kimko, Holly H. C.; Peck, Carl C. (Springer eBooks., 2011)
This edition presents a review of the principles and progress surrounding clinical trial simulations (CTS), along with case studies illustrating CTS in various therapeutic and application areas.  In addition, the book expands on the utility of CTS for informing decisions during drug development and regulatory review. Each chapter has been written by esteemed authors who have demonstrated expertise in state-of-the-art application of CTS.  The target audience for the volume includes researchers and scientists who wish to consider use of simulations in the design, analysis, regulatory review or guidance of clinical trials, and academic researchers and others working in drug development (e.g., clinicians, senior managers, project planning and regulatory affairs professionals). The focus is on the effective utilization  of CTS in decision mechanisms. Readers will gain broad knowledge on how CTS can improve the efficiency, informativeness, speed and economy of model-based drug development and regulation. Holly H.C. Kimko, PhD is a senior pharmacometrics leader (Research Fellow) at the Department of Advanced Modeling & Simulation in Johnson & Johnson Pharmaceutical Research & Development, LLC, New Jersey, and Adjunct Professor in the faculty of the Pharmacy School of Rutgers University, New Jersey.  She was previously Assistant Professor in the Center for Drug Development Science in Georgetown University Medical School, Washington DC. Trained in biochemistry and pharmacy, Dr. Kimko earned her Ph.D. degree in Pharmaceutical Science from the State University of New York, Buffalo.  She has published key papers on indirect response modeling and applications of CTS, and co-edited Simulation for Designing Clinical Trials. Carl C. Peck, MD is Adjunct Professor, Center for Drug Development Science in the Department of Bioengineering and Therapeutic Sciences, Schools of Pharmacy and Medicine, University of California San Francisco, California.  He was previously Director of the FDA Center for Drug Evaluation and Research, Assistant U.S. Surgeon General, and President of the American Society for Clinical Pharmacology and Therapeutics.  Dr. Peck has also held professorial appointments in the faculties of UCSF, USUHS, and Georgetown University.  He is an author of more than 150 original research papers, chapters and books concerning advanced concepts and techniques of quantitative pharmacology, trial designs, and pharmaco-statistical modeling and simulation.